Assessing power system security. A framework and a multi model approach. (December 2015) - Deane, J.P.; Gracceva, Francesco; Chiodi, Alessandro; Gargiulo, Maurizio; Gallachóir, Brian P.Ó.
Highlights: A multi model framework to assess system security is presented. System security is presented as a multidimensional property. Different dimensions of a secure energy system are correlated. Their behaviour cannot be explained by examining system elements in isolation. Abstract: This paper presents a methodological framework using a multi model approach to assess power system security. System security is viewed here as a multidimensional systemic property of the entire energy system. The paper shows that the different dimensions of a secure energy system are correlated, and hence their behaviour cannot be explained solely by an understanding of the individual dimensions or by system elements in isolation. The implication of this is that a proper assessment of the security of a power system requires a combination of different techno-economic models. The paper develops a comprehensive multi-model approach for investigating energy security issues within power systems, and applies it to a case study focussing on the Italian power sector. The core research activity involves using an energy systems model of Italy (MONET) to build a dedicated power systems model (PLEXOS_IT) and then undertaking a soft-linking exercise between the two models. The purpose is to use PLEXOS_IT to investigate the system adequacy of the power system results produced by MONET for future possible energy system scenarios.